2015
DOI: 10.1007/s00167-015-3556-1
|View full text |Cite
|
Sign up to set email alerts
|

The adductor tubercle: an important landmark to determine the joint line level in revision total knee arthroplasty

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 26 publications
0
25
0
1
Order By: Relevance
“…Intra-operative methods for locating the joint line using the epicondyles have been previously described: those reporting approximate distance values 5 , 21 or ratios. 2 , 10 , 17 , 22 , 23 The idea of creating ratios on this subject depends on the fact that owing to ethnic and anthropometric variation, the dimensions of the distal femur may differ between individuals. However, the ratio between the TEW and the epicondyle-joint line distance is not affected by anthropometric properties such as height and gender and was consistent between patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intra-operative methods for locating the joint line using the epicondyles have been previously described: those reporting approximate distance values 5 , 21 or ratios. 2 , 10 , 17 , 22 , 23 The idea of creating ratios on this subject depends on the fact that owing to ethnic and anthropometric variation, the dimensions of the distal femur may differ between individuals. However, the ratio between the TEW and the epicondyle-joint line distance is not affected by anthropometric properties such as height and gender and was consistent between patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, some authors have suggested that epicondyle determination may be difficult due to excessive soft tissues, fibrosis and scarring overlying the epicondyles, loss of bone and the operator-dependent factors associated with the surgeons’ ability to pinpoint identification accurately. 10 , 19 , 22 , 26 - 28 However, others have concluded that the epicondyles are reliable and easily identifiable intra-operative bony landmarks in TKA. 22 , 23 , 29 The superficial soft tissues covering the epicondyles can be dissected up to the collateral ligaments as a part of standard surgical exposure and debridement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das Verschiebung der Gelenklinie anhand verschiedener Landmarken evaluiert werden (30 % der transepikondylären Achse nach distal, Fibulaköpfchen, Tuberculum adductorium, Patellahöhen-stand) [45][46][47]. Auf den seitlichen Aufnahmen kann eine Veränderung des anterioren oder posterioren femoralen Offsets identifiziert werden.…”
Section: Diskussionunclassified
“…Determining the articular level using plain radiographs is possible by measuring the absolute distance between a reference bone landmark and the tangent to the JL. 7 The most commonly used bony landmarks are the epicondyles, tip of the fibula head, tibial tubercle and the inferior pole of the patella. 1 , 3 , 6 , 8 , 9 Recently, the adductor tubercle has been presented as a new bony landmark and the most useful, in determining the articular level in revision knee arthroplasty cases.…”
mentioning
confidence: 99%